2017
DOI: 10.1016/j.ebiom.2016.11.035
|View full text |Cite
|
Sign up to set email alerts
|

Paternal Insulin-like Growth Factor 2 (Igf2) Regulates Stem Cell Activity During Adulthood

Abstract: Insulin-like Growth Factor 2 (IGF2) belongs to the IGF/Insulin pathway, a highly conserved evolutionarily network that regulates growth, aging and lifespan. Igf2 is highly expressed in the embryo and in cancer cells. During mouse development, Igf2 is expressed in all sites where hematopoietic stem cells (HSC) successively expand, then its expression drops at weaning and becomes undetectable when adult HSC have reached their niches in bones and start to self-renew. In the present study, we aim to discover the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 62 publications
1
27
0
1
Order By: Relevance
“…In these stem cells, LOI presumably contributes to an increase in the stem cell pool and thus elevates the chances for a genetic mutation driving the cancerous transformation of these cells (Jelinic & Shaw, ; Leick et al , ). Furthermore, secretion of IGF2, which is encoded by an imprinted gene, was found to be important for hPSCs self‐renewal (Bendall et al , ) as well as for proliferation of several adult stem cells (Barroca et al , ; Youssef et al , ). These results suggest a special role for imprinted genes in regulating stem cell properties, therefore supporting the speculation that LOI might promote hPSC growth and survival in culture.…”
Section: Introductionmentioning
confidence: 99%
“…In these stem cells, LOI presumably contributes to an increase in the stem cell pool and thus elevates the chances for a genetic mutation driving the cancerous transformation of these cells (Jelinic & Shaw, ; Leick et al , ). Furthermore, secretion of IGF2, which is encoded by an imprinted gene, was found to be important for hPSCs self‐renewal (Bendall et al , ) as well as for proliferation of several adult stem cells (Barroca et al , ; Youssef et al , ). These results suggest a special role for imprinted genes in regulating stem cell properties, therefore supporting the speculation that LOI might promote hPSC growth and survival in culture.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, IGF‐2 is a maternally imprinted gene (H19‐IGF‐2 locus), and loss of imprinting leads to increased levels of IGF‐2, loss of HSC quiescence leading to a progressive loss of HSC, and increased number of downstream progenitors and differentiated cells due to increased differentiation rate . Conversely, loss of expression of paternal IGF‐2 has been shown to have opposite effects; reduction of HSC’ differentiation in favor of self‐renewal, resulting in increased numbers of HSC with cell‐autonomous long‐term (LT) engraftment defects . During development, IGF‐2 may also drive the HSC expansion phase at the fetal liver ontogenic stage.…”
Section: Introductionmentioning
confidence: 99%
“…The IGF2 gene, a member of the IGF/Insulin signaling, regulates cell proliferation, differentiation and survival (Barroca et al, ). As the lncRNA H19 has been shown to induce miR‐675 and to repress IGF‐1R and IGF‐2 (Zhou et al, ), we measured the expression levels of these two members of IGF signaling in neurally differentiated BMSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with earlier reports, our results indicated that H19 down-regulation is associated with reduced expression levels of miR-675 (Figure 4), suggesting that it may be this miRNA that confers functionality to H19 during neural differentiation of BMSCs. The IGF2 gene, a member of the IGF/Insulin signaling, regulates cell proliferation, differentiation and survival (Barroca et al, 2017). As the lncRNA H19 has been shown to induce miR-675 and to repress IGF-1R and IGF-2 (Zhou et al, 2015), we measured the expression levels of these two members of IGF signaling in neurally differentiated BMSCs.…”
Section: Discussionmentioning
confidence: 99%